PELAKSANAAN PENGAWASAN KEMETROLOGIAN TERHADAP PENGUSAHA-PENGUSAHA YANG MELAKUKAN KECURANGAN ALAT UKUR DI BALI - Diah Yupita Dewi, Made Ayu; Rai Setiabudhi, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 05, Juli 2014)
Metrology supervision and consumer protection should involve all parties that have arealionship and the interdependence of consumers as users of the goods or services of the worldas a producer. Purpose of this paper is to investigate the implementation of control metrologyentreoreneurs who commit fraud in official authority measuring instruments and industrial andtrade Bali is in giving legal sanction to offenders who commit fraud in measuring devices.Method in this research is to use the type of research that is empirical juridiction toconceptualize an empirical phenomenon that can be observed in real life. Of this study is thework done by the department of industrial and trade Bali is a measuring tool for tackling fraudis by monitoring is carried out properly, so as to provide protection to consumers and service ofindutrial and trade Bali is not authorized to impose sanctions on offerders attempt to commitfraud. Department of industrial and trade Bali province that has limite functions provideoversight and guidance.
Keywords: Implementation, Supervision, Metrology, Measuring Instruments